HLA‐E*0103X is associated with susceptibility to Pemphigus vulgaris. Issue 2 (31st January 2013) - Bhanusali, Dhaval G.; Sachdev, Amit; Rahmanian, Abootaleb; Gerlach, John A.; Tong, Joo Chaun; Seiffert‐Sinha, Kristina; Sinha, Animesh A.
Abstract: Non‐classical human leucocyte antigen‐E (HLA‐E) mediates natural killer and CD8+ T‐cell activity, suggesting a role in the regulation of autoimmunity. HLA‐E*0103X/*0103X has been associated with Behcet's disease and HLA‐E *0101/*0103X with childhood onset diabetes. We investigated HLA‐E allele status in 52 Caucasian and Ashkenazi Jewish Pemphigus vulgaris (PV) patients and 51 healthy controls by restriction fragment length polymorphism–polymerase chain reaction and amplification refractory mutation system. Associations were determined via chi‐square test, Fisher's exact test and logistical regression analysis. HLA‐E outcomes included presumed homozygous *0101/*0101 or *0103X/*0103X genotype status or *0101/*0103X heterozygous status. PV did not significantly associate with either *0101/*0101 or *0101/*0103X genotypes. HLA‐E*0103X/*0103X (presumed homozygote) is significantly increased in patients with PV versus controls ( P  = 0.0146, OR = 3.730, 95%CI = 1.241–11.213). Our data provide the first evidence that HLA‐E*0103X is a marker for genetic risk in PV.